Manajemen Pembiayaan Pendidikan dalam Meningkatkan Mutu Pembelajaran pada MTsN Ciwaringin Cirebon - Yusup Umar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
The purpose of this study is to find out and analyze about education financing management in improving the quality of learning at MTSN Ciwaringin Cirebon. This research uses a qualitative approach with a descriptive method. Its data collection techniques are with observation, interviews and documentation. Meanwhile, data analysis is by reducing data, displaying data and concluding data. The conclusion is:(1). The role of the principal in planning the source of education financing funds in accordance with the post that has been given by the government, (2). Education financing techniques prioritize the most vital things needed by school organizations, thereby improving the quality and quality of education (3). Supervision of education financing is carried out internally and externally. (4). The obstacles experienced, namely the first is the difference between planning and the costs received from the government, the second is that the payment of school committee money is not carried out regularly